Chemical composition, structural features, and physicochemical properties of starches from Thai indigenous rice varieties - Wichian Sangwongchai; Maysaya Thitisaksakul; Nitchakarn Sriwattana; Suphatta Phothiset; Duangkamon Sakloetsakun; Anoma Dongsansuk (International Journal of Food Properties)
Thai indigenous rice varieties provide valuable genetic resources due to their environmental resilience, but it is yet to be elucidated whether their endosperm starches are suitable for whole grain consumption or industrial applications. Here, 19 Thai indigenous rice starches were explored for compositional, structural, and physicochemical characteristics. Grain reducing sugar, protein, and amylose contents significantly differed among genotypes. Their starches were categorized as waxy, very low-, and low-amylose starches. The varieties with low-amylose starches displayed higher amylose content but lower crystallinity than the varieties with waxy and very low-amylose starches. The largest median starch granule size (d(0.5)) was also observed in most varieties with low-amylose starches. The starch compositional and structural variations contributed to substantial differences in starch physicochemical properties among these genotypes. The partial least squares discriminant analysis revealed that amylose content, setback, swelling power, reducing sugar, C- and A-type granules, d(0.5), and final viscosity could discriminate the low-amylose starches from the waxy and very low-amylose starches. Notably, correlation analyses revealed that amylose content was the most crucial factor determining starch physicochemical properties of these varieties. Starch compositional, structural, and physicochemical variations among the indigenous rice varieties can be adopted as alternative industrial raw materials and as genetic resources for future breeding programs.